2010
DOI: 10.1038/hdy.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Functional gametophytic self-incompatibility in a peripheral population of Solanum peruvianum (Solanaceae)

Abstract: The transition from self-incompatibility to self-compatibility is a common transition in angiosperms often reported in populations at the edge of species range limits. Geographically distinct populations of wild tomato species (Solanum section Lycopersicon (Solanaceae)) have been described as polymorphic for mating system with both self-incompatible and self-compatible populations. Using controlled pollinations and sequencing of the S-RNase mating system gene, we test the compatibility status of a population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Greater S‐RNase allelic diversity was recovered from mainland populations as compared to islands (20 vs. 3 alleles, respectively), and only two heterozygous genotypes were present in Hawaii compared to 18 heterozygous genotypes from the mainland. In addition, models incorporating diversifying selection are a more likely fit for S‐RNases from the mainland, which is consistent with previous studies in Lycium (Savage and Miller, ) and other genera (Igic et al., ; Miller and Kostyun, ) with functional gametophytic self‐incompatibility. Long‐distance dispersal followed by establishment on oceanic islands is thought to be relatively rare; thus, one might expect a genetic bottleneck at the S‐RNase locus (e.g., Miller et al., ; Nowak et al., ; Pannell, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Greater S‐RNase allelic diversity was recovered from mainland populations as compared to islands (20 vs. 3 alleles, respectively), and only two heterozygous genotypes were present in Hawaii compared to 18 heterozygous genotypes from the mainland. In addition, models incorporating diversifying selection are a more likely fit for S‐RNases from the mainland, which is consistent with previous studies in Lycium (Savage and Miller, ) and other genera (Igic et al., ; Miller and Kostyun, ) with functional gametophytic self‐incompatibility. Long‐distance dispersal followed by establishment on oceanic islands is thought to be relatively rare; thus, one might expect a genetic bottleneck at the S‐RNase locus (e.g., Miller et al., ; Nowak et al., ; Pannell, ).…”
Section: Discussionsupporting
confidence: 90%
“…Once alleles were designated, individual plants were assigned genotypes. Previous studies in self‐incompatible populations have demonstrated that models incorporating positive selection fit S‐RNase allelic data significantly better than corresponding models that do not incorporate positive selection (Savage and Miller, ; Igic et al., ; Miller et al., ; Miller and Kostyun, ). Following these studies, we used the codeml package in PAML (Yang, ) as implemented in PAMLX (Xu and Yang, ) to assess whether the pattern of selection on S‐RNase was consistent with results from our controlled crosses and previous studies documenting self‐incompatibility.…”
Section: Methodsmentioning
confidence: 99%
“…This process, known as pseudo-self-incompatibility, has also been reported in grasses in which artificial self-pollination techniques can contribute to SI breakdown (Do Canto et al, 2016). Similarly, sporadic fruit set has been observed across Solanaceae species such as Witheringia solanacea , S. carolinense , S. peruvianum , and N. alata in which floral age, flowering stage, and delayed floral abscission has been associated with fruit set in SI populations (Stone et al, 2006; Mena-Ali and Stephenson, 2007; Miller and Kostyun, 2011; Liao et al, 2016). This phenomenon has also been observed in species under sporophytic SI, in which floral age reduces the expression of the S -locus associated genes in Brassica oleracea resulting in SI breakdown (Hadj-Arab et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Crosses of S. peruvianum were performed as described in Miller & Kostyun () in an insect‐proof greenhouse. Briefly, pollen was collected from individual parental flowers by vortexing them in a microtube, and then applied onto the stigmas of flowers of the maternal parent.…”
Section: Methodsmentioning
confidence: 99%